Presidential decrees and department orders on education their implications for the Northern Luzon Teachers College - Constantino, Editha Burgos 1949- (1976)
Some educational directives and concerns from 1972 to 1975 should be considered in updating curricular offerings: the national development goals, economic and social progress, citizen's participation and enjoyment of such national growth and development, and national awareness and consciousness; the educational provisions of the 1973 Philippine constitution on adequate education, academic freedom, the teaching of the Constitution in all schools, love of country and citizenship, free elementary education, citizenship and vocational training, and Filipinization of capital and management of schools; directives on specific issues such as language, academic freedom, school and office publications, science, population, rice conservation and food production, livelihood, development of social concern and consciousness for better citizenry, and textbooks.
Appendices: leaves 188-384.
Mimeographed.
Thesis (M.A.)--University of the Philippines, Quezon City.
Vita.
Keywords: Northern Luzon Teachers College; Educational law and legislation -- Philippines; Teachers colleges -- Law and legislation -- Philippines